Determining of the Maximum Throughput of Control Valve in Heat Supply Systems - A. B. Sukhotski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2024)
Providing consumers with heat of the required quality in the required quantity is quitea tall order. This is due to various laws of time variation in thermal loads of residential, public and industrial buildings, and the high inertia of district heating systems. Currently, new technical capabilities have appeared that make it possible to implement methods of quantitative and qualitative regulation of heat load in heat supply systems, which have a number of advantages over qualitative regulation. Based on the equations of heat transfer, thermal and hydraulic balance, the article shows the interactions between the parameters of various types of heat supply systems, viz. valve opening degree, throughput capacity, flow rate, and coolant temperature. The type of flow characteristics of the control valve, temperature characteristics of heat supply systems, temperature control characteristics, thermal and hydraulic characteristics of the regulated area are determined. The purpose of the article was to consider the influence of the maximum throughput capacity of the control valve on the thermal and hydraulic characteristics of dependent and independent water heating systems. As a result of the analysis of the thermal and hydraulic characteristics of heating systems, recommendations have been developed for selecting valve parameters to ensure high-quality temperature control. For independent heat supply systems with a heat exchanger, it is recommended to install a control valve with a concave (logarithmic, parabolic or other) characteristic. In the case of installing a valve with a linear characteristic, the heat exchanger throughput capacity need to be greater than the maximum throughput capacity of valve (the pressure loss of the medium flow in open valve is higher than the pressure loss in the heat exchanger). For dependent heat supply systems, it is recommended to install a control valve with a linear characteristic and a maximum throughput capacity five times less than the throughput capacity of the jumper.